Asuhan Kebidanan Komprehensif Pada Ny. M Umur 35 Tahun Dengan Kekurangan Energi Kronis Di Wilayah Kerja Puskesmas Bantarkawung Kabupaten Brebes Tahun 2023 - Yuni Santika; Hafsah Hafsah; Mupliha Mupliha (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
According to WHO (2021) MMR is about 395,000 cases of deaths worldwide due to pregnancy and childbirth. According to ASEAN (2021) MMR is 235,000. Per 100,000 live births, In Indonesia the number of MMR is 7,389, cases, Central Java Province contributes to MMR 199 per 100,000 live deaths Brebes Regency 105 cases of MMR, Data from Bantarkawun Health Center in 2021 MMR 5 cases and IMR 4 cases. To find out how Comprehensive Midwifery Care on Mrs. M Age 35 Years With Chronic Energy Deficiency at the Puskesmas Bantarkawung Research Methods In this study, researchers used a qualitative descriptive method. From the care given to Mrs.M, no significant gaps were found. From the care that has been given to Mrs. M comprehensively from pregnancy, childbirth, postpartum, LBW, and family planning in the Bantarkawung Puskesmas work area and at Mrs.M's home, using the Varnay approach flow, and SOAP documentation.